Paintings, Publics, and Protocols: The Early Paintings from Papunya - Myers, Fred (Material Culture Review)

(untitled) (Cape Breton University Press, 2014)
Abstract The paintings in acrylic media in Central Australia are known for their capacity to objectify not only indigenous presence but also indigenous understandings of the world in the broader, surrounding society. However, this objectification of knowledge from a revelatory regime of value into one organized in other ways, is fraught with difficulty. Some paintings executed in the early period of this art movement are now considered inappropriate for general pubic exhibition because of their restricted esoteric meanings. The issue has been a controversial one in Australia, and museums and galleries must attend increasingly to developing protocols to satisfy Indigenous epistemological frameworks.